Temperature affects the production, activity and stability of ligninolytic enzymes in Pleurotus ostreatus and Trametes versicolor - Snajdr, J; Baldrian, P (Folia microbiologica, 2007)
Enzyme activity was determined in cultures of Pleurotus ostreatus and Trametes versicolor with cellulose as a sole C source and high C/N ratio. The fungi were able to grow and produce laccase and Mn-peroxidase (MnP) at 5-35 degrees C, the highest production being recorded at 25-30 degrees C in P. ostreatus and at 35 degrees C in T. versicolor. Production of both enzymes at 10 degrees C accounted only for 4-20% of the maximum value. Temperature optima for enzyme activity were 50 and 55 degrees C for P. ostreatus and T. versicolor laccases, respectively, and 60 degrees C for MnP. Temperatures causing 50% loss of activity after 24 h were 32 and 47 degrees C for laccases and 36 and 30 degrees C for MnP from P. ostreatus and T. versicolor, respectively.
Keywords: lakasa; lignin; Polyporales; Pleurotus; Laccase; Temperature; peroxidasy; Enzyme Stability; Fungal Proteins; Lignin; Peroxidases; fungální proteiny; teplota; stabilita enzymů